YIELD, QUALITY, NUTRIENT UPTAKE, SOIL FERTILITY AND WEED DRY WEIGHT AS INFLUENCED BY CASTOR ( ASTOR (RICINUS RICINUS COMMUNIS COMMUNIS L.) INTERCROPPED WITH MUNGBEAN ( L.) INTERCROPPED WITH MUNGBEAN (VIGNA RADIATA L.) UNDER DIFFERENT ROW RATIOS AND SPACIN - R. B. ARDESNA, A. K. KUMAWAT,; DINESH KUMAR,; M. CHOUHAN, (The Bioscan, 2016)
Experiment was conducted during rabi season of 2012-13 to study the response of castor (Ricinus communis L.) and mungbean (Vigna radiata L.) intercropping under different row spacing. The highest castor yield (2072 kg/ha) was found with sole castor (150 cm x 60 cm) while significantly higher stalk yield of castor (3545 kg/ha) was found with castor (120 cm x 60 cm) + mungbean (1:2). The highest oil content (45.26%) and oil yield (934 kg/ ha) of castor was recorded with treatment T3- sole castor (180 cm x 60 cm), whereas highest seed yield (1023 kg/ ha), stover yield (2614 kg/ha) and protein content (23.15%) of mungbean were recorded with T4- sole mungbean (40 cm x 10 cm). Whereas, higher available N and P2O5 in soil after harvest were observed with sole mungbean (40 cm x 10 cm). However significantly higher N uptake (56.43 kg/ha), P uptake (11.42 kg/ha) and K uptake (52.03 kg/ha) was observed with treatments T2 - sole castor (150 cm x 60 cm). Treatment T4 - sole mungbean (40 cm x 10 cm) recorded significantly lowest weed dry weight (2.90 g/m2 ) but did not differ significantly with treatment T5- castor (120 cm x 60 cm) + mungbean (1:2). Hence, intercropping of castor with mungbean in 1:2 ratio is recommended.